PENGARUH TEKNOLOGI TERHADAP PERKEMBANGAN ANAK USIA DINI - Elsa Yunisa; Maelasari Maelasari; Sri Rizki; Akhir Akhir; Imas Sa’diyah (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2024)
This academic research aims to prove and explain the changes that occurred in educational institutions in the era of globalization of the Industrial Revolution, so that educational institutions can compete globally through literary and analytical activities and contribute to this trend. Through future curriculum development we must equip students in academic dimensions and digital skills, apart from that teachers must have innovative teaching and educational competencies, learning media competencies that attract students' interest, globalization competencies, future strategy competencies, have a good sense of humor, funny and not monotonous, teaches holistically. Educational institutions must consider open and online learning when deciding on learning systems in educational institutions in order to take advantage of the challenges and opportunities of the industrial revolution in educational institutions. The research results show that there are several digital technology barriers that have been exploited, but there are still several uses of digital technology.